Does MaaS contribute to sustainable transportation? A mode choice perspective - Jang, Sunghoon; Caiati, Valeria; Rasouli, Soora; Timmermans, Harry; Choi, Keechoo (International Journal of Sustainable Transportation, 2020)
Mobility as a Service (MaaS) is an innovative concept, enabled by the ubiquitous availability of digital technologies. Many cities around the world envision MaaS as a way to improve sustainable transportation by reducing the use of fossil fuel-based transportation modes. However, MaaS may also trigger users of environmentally-friendly transportation modes to switch to less sustainable modes, such as taxi and ridesharing. The aim of this study is to explore how different bundling and pricing schemes of MaaS contribute to improving sustainable transportation. In order to analyze individuals’ intended choice of MaaS, a stated portfolio choice experiment was developed. A mixed logit model is estimated to investigate the bundle of transportation modes individuals configure when subscribing to MaaS. We explore empirical issues such as which transportation modes they prefer to include in the bundle, and how pricing schemes affect the composition of the bundle. Furthermore, scenario analyses are conducted to assess the impact of pricing schemes on sustainable transportation. Results show that MaaS contributes to improving sustainable transportation in a non-linear manner as a function of decreasing monthly subscription fees and/or increasing length of the subscription.
Keywords: Digital technologies; Mixed logit models; Portfolio choice; Pricing scheme; Ride-sharing; Scenario analysis; Sustainable transportation; Transportation mode; Mobility as a Service (MaaS); Stated Portfolio Choice Survey; Sustainable Transportation